Fabrication of a powder metallurgy Ti2AlNb-based alloy by spark plasma sintering and associated microstructure optimization. (5th January 2016) - Niu, H.Z.; Chen, Y.F.; Zhang, D.L.; Zhang, Y.S.; Lu, J.W.; Zhang, W.; Zhang, P.X.
Abstract: This study deals with preparing powder metallurgy Ti2 AlNb-based alloy via spark plasma sintering (SPS) technique. A pre-alloyed Ti2 AlNb-based alloy powder was produced by a plasma rotating electrode process (PREP), and then consolidated using SPS at temperatures between 900 °C and 1050 °C with a pressure of 50 MPa. Most of the pre-alloyed powder particles are characterized by single B2-phase dendrites. When the SPS temperature was 1000 °C or higher, the dendritic features and original boundaries of powder particles were removed, resulting in fully dense compacts. The as-sintered microstructure was modified by heat treatment to form fine acicular O-precipitates, leading to a superior yield strength of up to 1220 MPa at room temperature (RT). On the other hand, the heat treated microstructure with coarsened O-precipitates, produced via controlled slow cooling within the B2 + O phase field, exhibits a good RT elongation to fracture of 9.5%, but a relatively low yield strength of 840 MPa. Graphical abstract: Highlights: SPS is feasible to prepare Ti2 AlNb alloy using pre-alloyed spherical powders. SPS above 1000 °C produced highly dense B2-phase predominant microstructure. Superb strength was obtained via SPS and microstructural optimization. Strengthening and softening were realized via controlling O-phase precipitation.